Are US wages really determined by European labor-market institutions? - Jürgen Meckl (Institute for the Study of Labor (IZA), 2005)
This paper integrates institutionally determined wage rigidities into an otherwise standard Heckscher-Ohlin model of international trade. It accounts for differences in individual productivities and their implications for individual wage incomes and demand for education. Although preserving the factor-price-equalization property of the global equilibrium approach, the model does not support the view expressed by Davis (1998) that global equilibrium links insulate the US labor market from exogenous shocks. It provides a foundation of the derived from comparative studies that do not consistently account for the global general equilibrium links.
Keywords: F11; J31; 330; wage rigidities; international trade; education; skill-specific unemployment